2017
DOI: 10.4143/crt.2016.249
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Endpoints in Second-Line Trials of Targeted Agents in Metastatic Colorectal Cancer: A Literature-Based Systematic Review and Meta-Analysis

Abstract: PurposeThe purpose of this study was to evaluate progression-free survival (PFS) and objective response rate (ORR) as surrogate endpoints of overall survival (OS) in modern clinical trials investigating the efficacy of targeted agents in the second-line treatment of metastatic colorectal cancer (mCRC).Materials and MethodsA systematic search of literature pertaining to randomized phase II and III trials evaluating targeted agents as second-line treatments for mCRC was performed. The strength of the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…On the one hand, response rates could be a sensitive measure of benefit in the context of pediatric malignancies, given their rapid progression. On the other hand, the relationship between response rates and patient-centered outcomes like quality of life or survival is variable [ 33 37 ]. Moreover, eventual drug approvals are usually based on survival data from randomized controlled trials, and only about 6.7% to 9.6% of drugs tested in oncology will eventually be registered [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, response rates could be a sensitive measure of benefit in the context of pediatric malignancies, given their rapid progression. On the other hand, the relationship between response rates and patient-centered outcomes like quality of life or survival is variable [ 33 37 ]. Moreover, eventual drug approvals are usually based on survival data from randomized controlled trials, and only about 6.7% to 9.6% of drugs tested in oncology will eventually be registered [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…From each study, we extracted data related to study design, funding, reason for stopping the trial, patient characteristics, intervention, outcomes, and the timing of pediatric testing relative to adult testing. Because Phase I cancer studies do not generally have comparator arms or measure survival endpoints, we used objective response rate and the number of patients receiving recommended dose as proxies for therapeutic benefit [ 33 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The observatory main objective was to assess PFS and related predictive factors in routine clinical practice. PFS was chosen as the primary endpoint based on the results of several published analyses, demonstrating that PFS can act as a surrogate for OS in the first-line treatment metastatic colorectal cancer [ 9 , 10 ]. PFS is often chosen over OS in clinical trials as OS is impacted by the outcomes of subsequent therapeutic lines and does not directly evaluate the benefit of a given therapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…OS in the first-line treatment metastatic colorectal cancer [9,10]. PFS is often chosen over OS in clinical trials as OS is impacted by the outcomes of subsequent therapeutic lines and does not directly evaluate the benefit of a given therapy [11].…”
Section: Plos Onementioning
confidence: 99%
“…In their meta-analysis, Cremolini et al 7 confirmed the role of progression-free survival (PFS) as a reliable surrogate for OS, thus justifying the surrogacy of PFS as a primary endpoint in first-line studies in MCRC. Furthermore, the PFS has also been tested in second- and further-lines of treatment of several targeted agents producing significant results.…”
Section: Introductionmentioning
confidence: 99%